2018
DOI: 10.4196/kjpp.2018.22.6.607
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on cardio fibrosis in juvenile rats with pressure overload and deregulation of HDACs

Abstract: The effect of melatonin on juveniles with cardio fibrosis is poorly understood. We investigated whether HDACs participate in the anti-fibrotic processes regulated by melatonin during hypertrophic remodeling. Abdominal aortic constriction (AAC) was employed in juvenile rats resulting in pressure overload-induced ventricular hypertrophy and melatonin was subsequently decreased via continuous light exposure for 5 weeks after surgery. AAC rats displayed an increased cross-sectional area of myocardial fibers and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Previous studies showed the great therapeutic potential of HDAC inhibitors involved in the NSCLC treatment, and recent research findings reported that new class IIa HDAC inhibitors (eg, TMP195, TMP269, LMK235) are used in the cancer treatment studies . Interestingly, melatonin treatment could ameliorate the rat myocardial fibrosis caused by abdominal aortic constriction via reducing the expression of HDAC1, HDAC2, HDAC3, HDAC4, and HDAC6 . Moreover, Wei et al found that melatonin could induce apoptosis in colorectal cancer cells by promoting HDAC4 nuclear import.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the great therapeutic potential of HDAC inhibitors involved in the NSCLC treatment, and recent research findings reported that new class IIa HDAC inhibitors (eg, TMP195, TMP269, LMK235) are used in the cancer treatment studies . Interestingly, melatonin treatment could ameliorate the rat myocardial fibrosis caused by abdominal aortic constriction via reducing the expression of HDAC1, HDAC2, HDAC3, HDAC4, and HDAC6 . Moreover, Wei et al found that melatonin could induce apoptosis in colorectal cancer cells by promoting HDAC4 nuclear import.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the inhibition of HDAC3 has been previously shown to suppresses myocyte hypertrophy and alleviate LVHF in animals [ 13 ]. After instilling melatonin treatment, the cardio fibrosis along with the gene expressions of HDAC1 (1, 2, 3, 4, 6) are both alleviated [ 41 ]. Furthermore, inhibition of HDAC3 can improve cell viability and alleviate apoptosis in cerebral ischemia reperfusion injury mice in diabetic state [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the response to long-standing arterial hypertension, heart function is maintained through enlarged cardiomyocytes and increased protein synthesis, accompanied by the reactivation of the fetal gene expression, such as ANF, which are the characteristics of cardiac hypertrophy. The abdominal aorta is constricted to increase cardiac pressure overload and induce cardiac hypertrophy, which is more clinically relevant and similar to the human form of the disease [ 9 , 14 ]. Numerous studies have found that the left ventricular hypertrophy was developed on the 4th week after AAC in rats, which was similar to the results in the present study (data not shown).…”
Section: Discussionmentioning
confidence: 99%